Bedtime doses of prazosin do not affect daytime salivary amylase markers in PTSD. Issue 5 (May 2019) - McCall, William Vaughn; Pillai, Anilkumar; Pandya, Chirayu D.; McCloud, Laryssa; Moraczewski, Jason A.; Tauhidul, Liniya; Youssef, Nagy A.; Case, Doug; Rosenquist, Peter B.
Abstract: Overactivity of the noradrenergic (NE) system within the central nervous system (CNS) has been postulated as a key pathophysiology of posttraumatic stress disorder (PTSD). The activity of the enzyme salivary α-amylase (sAA) has been proposed as an indirect measure of CNS NE activity, and sAA is elevated in PTSD. As an antagonist of the α-1 NE receptor, prazosin would be expected to alter sAA values in PTSD patients. However, given its short half-life, it is not clear whether bedtime doses would have an effect on daytime sAA. In the present study, we assayed daytime sAA in 20 suicidal PTSD patients who were randomized to prazosin versus placebo at bedtime-only, and found no effect in daytime sAA. These findings are consistent with studies showing an advantage for twice daily dosing of prazosin in PTSD.